Two step microwave plasma carbonization including low plasma power pre-carbonization for polyacrylonitrile based carbon fiber - Kim, Seong Yun; Kim, So-Young; Choi, Jisung; Lee, Sungho; Jo, Seong Mu; Joo, Junghoon; Lee, Hun-Su (ELSEVIER SCI LTD, 2015)
Reducing the price of carbon fiber (CF) is crucial to the wider application of CFRP in automobiles for energy reduction. Because process costs account for 46% of the total cost of CF, interest has increased in the development of affordable processes such as microwave plasma carbonization, which can reduce the cost. In this study, the concept of a two step microwave plasma carbonization process is suggested to enhance the mechanical properties of the CF made with the plasma process. Compared with single step carbonized CF, the two step carbonized CF had 171% improved tensile strength because of the synergetic effect of the low power and high power carbonization steps. Two step or multi step carbonization process is expected to be another improvement of the microwave plasma carbonization process in that it not only reduces the energy consumption of the process but also improves the mechanical properties of CF. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: NANOTUBES; STABILIZATION; PRECURSORS; OXIDATION